(untitled) (Psychology Travelogs, 2025)
The article analyses the works of leading foreign psychologists on building personal integrity. Analyzing research on the process of achieving personal integration, the general idea is that this process is a way to overcome threats of losing personal integration or achieving higher states, and is not a goal in itself. The authors describe it through the processes of overcoming crises, self-knowledge, satisfying existential needs, personal growth, achieving self-actualisation, and developing a range of abilities, including creative ones. When analysing research on the process of achieving personal integration, it is common that this process is a way to overcome threats to personal integration or achieve higher states, rather than being the goal itself. In the process of researching the processes of building personal integration, the following groups have been identified: factors that pose threats to personal integration; ways to achieve personal integration; research into processes where achieving personal integration is a means to achieve higher goals. Factors that pose a threat to personal integrity can be divided into the following categories: individual, collective and professional. Ways to build and maintain personal integrity can be considered in two aspects: substantive change in the content of values and integrative work of the personality to restructure the elements of the value system. Integrity in terms of identity support is a process that ensures the achievement of internal consistency between values and between values and human actions. The success of the integration process creates a stable state of internal consistency – this is personal integrity itself. And the stable reproduction and maintenance of the state of integrity develops into a property, a quality of personality, which can be appropriately called a personality trait.